Genetic diversity and genetic structure of Puya raimondii (Bromeliaceae) for its conservation in the Peruvian Andes - Tumi, Liscely (2022)
Puya raimondii is an endemic species from the high Andes of Peru and Bolivia. In Peru it is distributed from 8.068501°S, 16.170280°W to 16.180580°S, 70.658873°W, between 3600 and 4800 m, living in extreme climatic conditions typical of the Puna, where it plays an important ecological role. Despite the wide distribution of P. raimondii populations in Peru, they appear to be fairly uniform morphologically. The following questions arise: Will the current molecular tools be able to show differences between the numerous populations? Are the conservation areas established for P. raimondii sufficient since they harbor the existing variability? To answer these questions, this work aimed to evaluate the genetic diversity and genetic structure in a northern population, Pachapaqui (Ancash department), a central population, Yanacancha (Junin), and a southern population, Lampa - Choconchaca sector (Puno), using microsatellite markers (SSR) specific for the species. The genetic diversity parameters used included number of alleles (A), exclusive alleles (RA), observed heterozygosity (Ho), expected heterozygosity (He), and polymorphic content index (PIC). The results showed that the total number of A varied from 2 - 13, the He values were 0 ‒ 0.723 and Ho 0 ‒ 0.929, with an average He of 0.217, indicating a moderate to high genetic diversity, being the population of Lampa-Choconchaca sector, the one that presented the greatest allelic diversity and the greatest genetic diversity. The Hardy-Weinberg test showed that the populations are in HW disequilibrium, the statistical analysis indicates 65% of the genetic variation at the population level and values of FST (0.426) and RST (0.650) that indicate high genetic differentiation among populations, with two genetic groups (K=2) that correspond to the populations of northern-central and southern Peru. The results provide useful information to establish conservation strategies for P. raimondii, which lead to the creation of an additional conservation area to protect the populations in southern Peru.